Montréal une ville festive pour toutes: Avis sur la sécurité des femmes et des jeunes femmes cisgenre et trans lors des événements extérieurs à Montréal - Conseil des Montréalaises (2017)
Keywords: Bibliographie; Camille; Nettoyer

A Balancing Act: Agency and Constraints in University Students’ Understanding of and Responses to Sexual Violence in the Night-Time Economy - Anitha, Sundari; Jordan, Ana; Jameson, Jill; Davy, Zowie (Violence Against Women, 2021)
This article extends our understanding of how university students make sense of, and respond to, sexual violence in the night-time economy (NTE). Based on semi-structured interviews with 26 students in a city in England, we examine students’ constructions of their experiences of sexual violence within the NTE, exploring their negotiations with, and resistance to, this violence. Building upon theories of postfeminism, we interrogate the possibilities for resistance within the gendered spaces of the NTE and propose a disaggregated conceptualization of agency to understand responses to sexual violence, thereby offering useful insights for challenging sexual violence in the NTE and in universities.
Keywords: Camille

“Blurred Lines?” Sexual Aggression and Barroom Culture - Graham, Kathryn; Bernards, Sharon; Osgood, D. Wayne; Abbey, Antonia; Parks, Michael; Flynn, Andrea; Dumas, Tara; Wells, Samantha (Alcoholism, clinical and experimental research, 2014)
Background Meeting potential sexual/romantic partners for mutual pleasure is one of the main reasons young adults go to bars. However, not all sexual contacts are positive and consensual, and aggression related to sexual advances is a common experience. Sometimes such aggression is related to misperceptions in making and receiving sexual advances while other times aggression reflects intentional harassment or other sexually aggressive acts. The present study uses objective observational research to assess quantitatively gender of initiators and targets and the extent that sexual aggression involves intentional aggression by the initiator, the nature of responses by targets, and the role of third parties and intoxication. Methods We analyzed 258 aggressive incidents involving sexual advances observed as part of a larger study on aggression in large capacity bars and clubs, using variables collected as part of the original research (gender, intoxication, intent) and variables coded from narrative descriptions (invasiveness, persistence, targets’ responses, role of third parties). Hierarchical Linear Modeling (HLM) analyses were used to account for nesting on incidents in evening and bars. Results 90% of incidents involved male initiators and female targets, with almost all incidents involving intentional or probably intentional aggression. Targets mostly responded nonaggressively, usually using evasion to end the incident. Staff rarely intervened; patron third parties intervened in 21% of incidents, usually to help the target but sometimes to encourage the initiator. Initiators’ level of invasiveness was related to intoxication of the targets but not their own intoxication, suggesting intoxicated women were being targeted. Conclusions Sexual aggression is a major problem in bars often reflecting intentional sexual invasiveness and unwanted persistence rather than misperceptions in sexual advances. Prevention needs to focus on addressing masculinity norms of male patrons and staff that support sexual aggression and better management of the highly sexualized and sexist environments of most bars.
Keywords: Camille

Bar Training for Active Bystanders: Evaluation of a Community-Based Bystander Intervention Program - Powers, Ráchael A.; Leili, Jennifer (Violence Against Women, 2018)
Bystander intervention programs are proliferating on college campuses and are slowly gaining momentum as sexual violence prevention programs suitable for the larger community. In particular, bystander intervention programs aimed at bar staff have been developed in a number of locations. This study entails the exploratory evaluation of a community-based bystander program for bar staff. Using a pre–posttest design, this study suggests that evidence surrounding the effectiveness of this program is promising as it decreases rape myths, decreases barriers to intervention, and increases bartenders willingness to intervene. Future research and policy implications are discussed.
Keywords: Camille

"Yeah, We Serve Alcohol, but … We Are Here to Help": A Qualitative Analysis of Bar Staff's Perceptions of Sexual Violence - Powers, Ráchael A.; Leili, Jennifer (Violence and Victims, 2016)
This study is an exploratory analysis of how bar staff perceive their role in preventing sexual harassment and assault. In particular, through qualitative focus group interviews, this study explores bar staff's attitudes surrounding sexual harassment/assault, how they currently handle these situations, and their opinions regarding programs and policies that currently mandate responsibility. Six major themes emerged including their hesitation to discuss sexual violence, their unique position as a service provider, their lack of knowledge (but eagerness to learn), and their reliance on stereotypical scenarios of sexual violence and interventions. These findings are situated in a framework for understanding barriers to bystander intervention and implications for community-based bystander programs are discussed.
Keywords: Adult; Camille; Female; Focus Groups; Helping Behavior; Humans; Interpersonal Relations; Male; Rape; Restaurants; Sex Offenses

Unwanted Sexual Attention in Licensed Venues: Considering LGBTIQ Young Adults' Experiences and Perceptions - Fileborn, Bianca (2015)
English Abstract: Sexual violence within the lesbian, gay, bisexual, transgender/transsexual, intersex and queer (LGBTIQ) communities remains largely under-researched and under-theorised. Yet, emerging research suggests that sexual violence is a significant issue within the LGBTIQ communities. Additionally, the occurrence of sexual violence and unwanted sexual attention within specific social and cultural contexts is, for the most part, insufficiently examined. This article draws on research exploring young LGBTIQ adults’ perceptions and experiences of unwanted sexual attention in licensed venues. Firstly, I consider the theoretical and conceptual underpinnings of ‘unwanted sexual attention’ as a category of analysis. I then move on to consider participants’ use of licensed venues, the particular significance of pubs and clubs to LGBTIQ young people, and their perceptions and experiences of unwanted sexual attention. Finally, I discuss the implications of these findings for theoretical and conceptual understandings of unwanted sexual attention and sexual violence.
Keywords: Camille; Gender; Género; LGBTIQ; economía nocturna; licensed venues; locales con licencia; night time economy; orientación sexual; sexual orientation; sexual violence; violencia sexual

Gendered Responses to Gendered Harms: Sexual Violence and Bystander Intervention at Australian Music Festivals - Baillie, Greta; Fileborn, Bianca; Wadds, Phillip (Violence Against Women, 2022)
Bystander intervention has shown promise in preventing sexual violence in certain social contexts. Despite emerging evidence of pervasive sexual violence at music festivals, no research has considered bystander intervention in this setting. Drawing on an online survey conducted with 371 Australian festival attendees, we explore the role of gender on bystander intervention at music festivals. Findings point to significant gender differences, with women more willing and likely to intervene in a broader range of scenarios. We argue that responses to sexual violence are a collective responsibility shared by both women and men, as well as festival organizers and industry bodies.
Keywords: Camille

Safety, sexual harassment and assault at Australian music festivals: final report - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (2019)
Keywords: Camille

‘Staff can't be the ones that play judge and jury’: Young adults’ suggestions for preventing unwanted sexual attention in pubs and clubs - Fileborn, Bianca (Australian & New Zealand Journal of Criminology, 2017)
This paper explores young adults' suggestions for preventing unwanted sexual attention in licensed venues. Despite emerging evidence that unwanted sexual attention and sexual violence are significant issues faced by young adults in the night-time economy, there has been little introduced in the way of preventative strategies or campaigns. Drawing on a mixed-methods research project undertaken in Melbourne, Australia, I contend that exploring young adults' suggestions for prevention is instructive in a number of ways. Young adults are the primary users of licensed venues and thus may provide insight into potential strategies for prevention. It can also illuminate the discursive positions that young adults draw on in talking about prevention and their understandings of unwanted sexual attention.
Keywords: Camille

Sexual harassment and violence at Australian music festivals: Reporting practices and experiences of festival attendees - Fileborn, Bianca; Wadds, Phillip; Tomsen, Stephen (Australian & New Zealand Journal of Criminology, 2020)
Despite the well-documented under-reporting of sexual violence, to date, no research has considered reporting practices within the specific context of music festivals. Drawing on 16 in-depth interviews with victim-survivors, this article examines survivors’ experiences of (non)reporting sexual violence in festival settings. We argue that while some barriers to reporting are shared across contexts, others play out in context-specific ways. Our research argues that the liberal, often transgressive culture of music festivals, combined with site-specific policing practices and spatial context, creates unique impediments to reporting with particular implications in responding to, and aiming to prevent, sexual violence at music festivals.
Keywords: Bibliographie; Camille; Nettoyer

Doing gender, doing safety? Young adults’ production of safety on a night out - Fileborn, Bianca (Gender, Place & Culture, 2016)
This article explores the ways in which young adults produce a sense of safety in pubs and clubs. Despite considerable anxiety around issues pertaining to safety and violence in the night-time economy, there is little consideration of how young adults themselves feel about their safety on a night out, or how they achieve a sense of safety in a seemingly ‘risky’ social space. Drawing on mixed-methods research conducted in Melbourne, Australia, in this article I consider the strategies that young adults used to feel safe on a night out. I argue that feeling ‘safe’ is something that is actively produced through the use of these strategies, as well as providing an avenue for ‘doing’ gender.
Keywords: Camille; Safety; Seguridad; economía nocturna; feminidad; femininity; gender performance; licensed venues; locales autorizados; masculinidad; masculinity; night-time economy; performance de género; 夜间经济; 女性气质; 安全; 性别展演; 拥有许可证之营业场所; 男性气概

Sex and the City: Exploring Young Women's Perceptions and Experiences of Unwanted Sexual Attention in Licensed Venues - Fileborn, Bianca (Current Issues in Criminal Justice, 2012)
Recent research has highlighted the need to explore how specific social contexts influence the occurrence of sexual violence and sexually harassing behaviours. This article considers the occurrence of unwanted sexual attention towards young women within the social context of licensed venues in Melbourne, Victoria. Using focus group data from a small qualitative study, three ‘characteristics’ of unwanted sexual attention are considered: the forms this behaviour takes and how it impacts young women; the nature of the relationship between victim and perpetrator; and the role of venue culture in facilitating this behaviour. It is argued throughout this article that an intersection of broader social norms and the specific social norms and cultural mores of licensed venues creates a social environment that can facilitate the occurrence of unwanted sexual attention, and that restrains the ways in which young women are able to respond to these experiences.
Keywords: Camille

Reclaiming the Night-Time Economy - Fileborn, Bianca (Palgrave Macmillan UK, 2016)
Keywords: Alcohol; Assemblage; Camille; Community; Crime prevention; Criminology; Culture; Drugs; Environmental design; Gender; LGBTIQ; Licensed venues; Safety; Sexual consent; Sexual ethics; Sexual offending; Sexual violence; Sexuality; Space; Young people

Sexual violence at live music events: Experiences, responses and prevention - Hill, Rosemary Lucy; Hesmondhalgh, David; Megson, Molly (International Journal of Cultural Studies, 2020)
Recent media reporting has highlighted that incidents of sexual violence frequently occur at live music events. Sexual violence has significant impacts on the health of those who experience it, yet little is known of how it impacts on everyday engagements with music, nor what measures venues and promoters might take to prevent and respond to incidents. Through interviews with concert goers, venue managers, promoters and campaigning groups, we investigated experiences of sexual violence at indie, rock, punk and funk gigs in small venues in one English city. We show that sexual violence at live music events significantly impacts on (predominantly) women’s musical participation. We argue that venues and promoters must work proactively to create musical communities that act as a defence against the normalisation of sexual violence, taking inspiration from safer space policies.
Keywords: Camille; gender; live music; prevention; safe spaces; sexual violence; unwanted sexual attention

Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events - Fileborn, B.; Wadds, P.; Barnes, A. (2019)
Setting the Stage for Sexual Assault: The Dynamics of Gender, Culture, Space and Sexual Violence at Live Music Events
Keywords: Camille